Implementation of Manual and Digital Financial Management on BUMDes in Cimanggis Village, Bojong Gede, Bogor Regency, West Java, Indonesia - Mahendro, Mahendro; Manggabarani , Alfatih S.; Marzuki, Faisal (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
BUMDes Cimanggis tries to be a solution for empowering the potential of the village. However, there are obstacles regarding financial management because human resources do not yet have the ability and expertise in the field of accounting. Though the financial aspect is a sensitive matter. It is feared that unaccountable financial management will become a serious problem in the future, such as ignorance of financial position, unclear cash flows, making financial statements that are less informative so that the report cannot be used as a basis for making financial decisions. This results in unprofessional and non-transparent BUMDes management, resulting in the loss of public trust. The purpose of this research and community service is to provide training or workshops on manual and digital accounting to BUMDes Cimanggis managers in order to improve better and accountable financial management. The methods used in this research and community service are lectures, discussions, workshops, mentoring and the application of manual and digital accounting. The expected result is that BUMDes can become a professional and transparent body in financial management as one of the determining factors for good managerial.